Developing a Crisis Management Training Model for Reducing Air Traffic Control Challenges in Iran - Sepehri, Setareh; Shirzad Kebria, Baharak; Saffariyan Hamedani, Saeid; Kordestani, Fereshteh (Iranian Journal of Educational Sociology, 2026)
Purpose: This study aimed to develop and validate a crisis management training model designed to reduce the challenges affecting air traffic control operations.Methods and Materials: This applied study employed an exploratory sequential mixed-methods design consisting of qualitative and quantitative phases. In the qualitative phase, an emergent grounded theory approach was used. Nineteen experts in air traffic control, crisis management, and educational management were selected through purposive sampling and interviewed using semi-structured interviews. In the quantitative phase, a descriptive-survey design was adopted. The statistical population comprised 430 air traffic control personnel working at Mehrabad Airport Control Tower, Tehran Approach Control, and the Area Control Center. Using Cochran’s formula and stratified random sampling, 203 participants were selected. Qualitative data were analyzed in MAXQDA, while quantitative data were examined through structural equation modeling using SPSS and AMOS. Data were collected using a researcher-developed questionnaire whose face, content, and construct validity and internal consistency reliability were confirmed.Findings: The qualitative analysis generated a model comprising five dimensions, 19 components, and 93 indicators. Structural equation modeling supported the proposed measurement and structural model and confirmed the significant contribution of the five principal dimensions to crisis management training. These dimensions were operational preparedness and capability; crisis management and rapid response; leadership, structure, and resources; knowledge and continuous learning; and emerging technologies. The model demonstrated that simulation-based training, safety management, navigational resilience, cybersecurity, communication, climatic preparedness, risk prioritization, command structure, occupational health, human resources, legal and strategic frameworks, training sustainability, meteorological information, and intelligent data analysis were significant components of an integrated crisis management training system.Conclusion: The validated model provides a comprehensive and operational framework for strengthening crisis preparedness, improving rapid-response capacity, and reducing air traffic control challenges in Iran.